H39 Prospects for exercise and physical activity in huntington's disease hd – what next?. (September 2018) - Busse, Monica; Quinn, Lori; Dimitropoulou, Polyxeni; Kelson, Mark; Playle, Rebecca
Abstract : Background: This speaker presentation will interpret results of an individual patient data meta-analyses (IPD-MA) of a range of randomized controlled feasibility trials with the aim of exploring prospects for exercise and rehabilitation in Huntington's Disease (HD). Methods: Participants(n=121) in five randomised physical activity and/or exercise trials engaged in a combination of supervised and self-directed exercise and physical activity interventions with varied emphasis on aerobic, strength, endurance, flexibility and task training across interventions and duration ranged from eight to 16 weeks. The primary outcome in the combined dataset was the modified Unified Huntington's Disease Rating Motor Score (mMS). There were a range of secondary outcomes. Primary pooled effect estimates were examined via a cross-classified linear mixed model. A random effects model was used to account for study heterogeneity. Results: There was significant heterogeneity between the studies. Risk of bias was moderate in these open trials; however, the primary motor outcome was collected blind. A favourable motor outcome was associated with individual studies where supervision was an important component of the intervention. There were no effects on motor outcome in the pooled data. Of the pooled effects for secondary outcomes, self-reported physical activity was significantly improved. Conclusions: Self-reported physical activity increased following participation in short duration supervised and self-directed exercise and physical activity interventions but this did not translate into motor benefits in HD. Longer duration intervention trials that incorporate supervised components meeting frequency, intensity, time and type (FITT) principles for exercise prescription are required. The importance of a defined intervention, appropriate supervision and related core outcome set (including patient reported outcomes) in HD cannot be understated.